2022
DOI: 10.1186/s12936-022-04164-z
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to accept malaria vaccine among caregivers of under-5 children in Southwest Ethiopia: a community based cross-sectional study

Abstract: Background Malaria is widespread in Ethiopia and has been a major cause of illness and death in that country. Therefore, Ethiopia has been exerting enormous efforts towards eliminating malaria by 2030. In the context of comprehensive malaria control, the malaria vaccine is used for the prevention of Plasmodium falciparum malaria in children living in regions with moderate- to-high malaria transmission. Methods A community-based cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 24 publications
3
38
1
Order By: Relevance
“…Interventions with no cost have been shown to be more successful in achieving coverage. Studies on the willingness to pay for malaria vaccines show that target populations have reduced willingness to pay for the vaccine, and acceptance would be higher if it is provided for free [ 27 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions with no cost have been shown to be more successful in achieving coverage. Studies on the willingness to pay for malaria vaccines show that target populations have reduced willingness to pay for the vaccine, and acceptance would be higher if it is provided for free [ 27 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study suggests that the Nigerian population will be accepting of receiving the malaria vaccine, there are a number of factors associated with the acceptance of the vaccine, such as cultural practices, efficacy, beliefs and the existence of adverse impacts of the vaccine [ 36 38 ]. Asmare showed that mothers may not be willing to vaccinate their children against malaria since they believe that the vaccine may harm their children, it may be expensive and their husbands will not allow their children to be vaccinated [ 35 ]. It is, therefore, important to increase knowledge through the education and support of the populace in accepting and increasing awareness of the potential benefits and adverse impacts of being vaccinated against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions with no cost have been shown to be more successful in attaining coverage. The studies on the willingness to pay for malaria vaccine showed that target populations have reduced willingness to pay for the vaccine and the acceptance would be higher if it is provided for free [27,35].…”
Section: Main Ndingsmentioning
confidence: 99%
“…Although this study is suggesting that Nigerian population will be accepting to receive malaria vaccine, there are a number of factors associated with the acceptance of the vaccine, such as cultural practices, e cacy, beliefs and the existence of any adverse impact of the vaccine. Asmare showed that mothers may not be willing to vaccinate their children against malaria, since they have thoughts that the vaccine may harm their children, it may be expensive and their husbands will not allow their children to be vaccinated [35]. It is, therefore, important to build a knowledge by education and support of the populace in accepting and having awareness on the potential bene ts and adverse impacts of being vaccinated against malaria.…”
Section: Main Ndingsmentioning
confidence: 99%
“…While the development of a vaccine to prevent this deadly disease shows great promise, human mortality is still predicted to increase [ 30 , 31 ]. This is due in part to low vaccination rates in young children, and also due to evolutionary processes that drive parasite resistance against the currently available antimalarial drugs [ 32 ]. Thus, new therapeutics will continually be needed to treat infected patients.…”
Section: Introductionmentioning
confidence: 99%